Sharia and Politics in The Context of Globalization and Society 5.0 - Masykuri Abdillah (AHKAM : Jurnal Ilmu Syariah, 2022)
This article aims to describe and analyze globalization and its impact on Islamic politics and Islamic law (sharia) in the modern era. Globalization has brought about a new set of ethics and norms in human relations which in some ways have led to changes in worldviews as well as social, economic, and political systems in the world. Most Muslim scholars accept it, including the  influence  of Western  civilization,  with  certain  adjustments  that  refer  to Islamic teachings and national identity. In most Muslim countries, globalization has  affected  changes  in  state  systems,  such  as  nation-state,  democracy,  and protection of human rights. In addition, globalization has affected the status of Islamic law, especially in the form of secularization of national law, although this was later revised with efforts of Islamization of national law. Globalization also  has  an  impact  on  the  need  to  reinterpret  several  provisions  of  Islamic law that are not in line with modern perspectives and challenges, especially provisions  related  to  society  5.0,  such  as  legitimizing  digital  transactions, peaceful relations between Muslims and non-Muslims, and the understanding of defensive jihad.Keywords: globalization; Islamic politics; Islamic law AbstrakArtikel  ini  bertujuan  untuk  mendeskripsikan  dan  menganalisis globalisasi dan dampaknya terhadap politik Islam dan hukum Islam (syariah) di era modern. Globalisasi telah membawa seperangkat etika dan norma baru dalam hubungan manusia yang dalam beberapa hal menyebabkan perubahan pandangan dunia serta sistem sosial, ekonomi, dan politik di dunia. Sebagian besar  ulama  dan  intelektual  Muslim  menerimanya,  termasuk  pengaruh peradaban  Barat,  dengan  penyesuaian  tertentu  yang  mengacu  pada  ajaran Islam dan identitas bangsa. Di sebagian besar negara Muslim, globalisasi telah mempengaruhi perubahan sistem negara, seperti nation-state, demokrasi, dan perlindungan hak asasi manusia. Selain itu, globalisasi telah mempengaruhi status  hukum  Islam,  terutama  dalam  bentuk  sekularisasi  hukum  nasional, meskipun kemudian direvisi dengan upaya Islamisasi hukum nasional. Globalisasi  juga  berdampak  pada  kebutuhan  untuk  menafsirkan  kembali beberapa  ketentuan  hukum  Islam  yang  tidak  sejalan  dengan  perspektif  dan tantangan modern, terutama ketentuan yang terkait dengan masyarakat 5.0, seperti legitimasi transaksi digital, hubungan damai antara Muslim dan non- Muslim, dan pemahaman tentang jihad defensif.Kata Kunci: globalisasi; politik Islam; hukum Islam